Dampak Pelaksanaan Otonomi Daerah terhadap Kesejahteraan Masyarakat Jawa Tengah - Hariadi, Pramono (Jurnal Trikonomika, 2010)
This study aims to determine the relationship of community welfare after implementation of regional autonomy. The study which located in Central Java Province is use secondary data analysis. Data Collection Method was Library Study and data compilation that come from: BPS, Dipenda, BAPPEDA and other data sources related. Hypothesis tested by Structural Equation Modelling (SEM). The results showed that the implementation of regional autonomy in Central Java has a positive impact on the welfare of the community with markers Human Development Index (HDI), literacy rates, income per capita and public health. Mean that regional autonomy has reached the goal, but improvements still needed in order to achieve a better degree of autonomy.